RELATIONSHIP BETWEEN AQUATIC METHODS IN PATIENTS WITH DUCHENNE MUSCULAR DYSTROPHY (REMUNOM, 2024)
Duchenne muscular dystrophy (DMD) is a genetic disease that mainly affects boys, resulting in progressive loss of muscle strength, with symptoms beginning between 3 and 5 years of age. Aquatic physiotherapy focuses on maintaining functionality and preventing complications. Despite interventions, patients' quality of life is impacted, including physical, psychological and social aspects. This study reviewed how physiotherapy can benefit the quality of life of patients with DMD. The article is a literature review that analyzes aquatic methods for patients with Duchenne muscular dystrophy. Databases such as BVS, Lilacs and PubMed were used, with a search for articles from the last 10 years in English, Portuguese, Spanish and German. Three articles were selected. Improvements were found in the performance of functional mobility tasks in and out of water, along with improvements in inspiratory and expiratory volumes, which could indicate a possible relationship between aquatic exercise in DMD and respiratory functions related to functional participation.Keywords:  Duchenne muscular dystrophy; Aquatic therapy; Aquatic physiotherapy